2014
DOI: 10.2214/ajr.13.10644
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Ultrasound: CT and MRI of Ectopic Pregnancy

Abstract: Various types of ectopic pregnancy have characteristic imaging features. Radiologists should be familiar with these features and should always consider the possibility of ectopic pregnancy in the setting of hemoperitoneum or a pelvic mass in a woman of child-bearing age. Familiarity with the typical CT and MRI appearances of various forms of ectopic pregnancy facilitates prompt and accurate diagnosis and treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
67
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(72 citation statements)
references
References 39 publications
0
67
0
1
Order By: Relevance
“…In humans, diagnosis of ectopic pregnancy includes analysis of serum β-human chorionic gonadotropin and progesterone levels, ultrasonography, diagnostic laparoscopy, and endometrial biopsy, among others (Corpa 2006;Sivalingam et al 2011). Although ultrasonography is the most preferred method in the diagnosis of ectopic pregnancy, CT or magnetic resonance imaging (MRI) can also provide sufficient evidence to make a diagnosis if clinical prediction has not been confirmed (Anderson et al 2009;Kao et al 2014). CT and MRI methods allow more accurate and rapid diagnosis by dint of sectional imaging (Febronio et al 2012;Kao et al 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In humans, diagnosis of ectopic pregnancy includes analysis of serum β-human chorionic gonadotropin and progesterone levels, ultrasonography, diagnostic laparoscopy, and endometrial biopsy, among others (Corpa 2006;Sivalingam et al 2011). Although ultrasonography is the most preferred method in the diagnosis of ectopic pregnancy, CT or magnetic resonance imaging (MRI) can also provide sufficient evidence to make a diagnosis if clinical prediction has not been confirmed (Anderson et al 2009;Kao et al 2014). CT and MRI methods allow more accurate and rapid diagnosis by dint of sectional imaging (Febronio et al 2012;Kao et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Although ultrasonography is the most preferred method in the diagnosis of ectopic pregnancy, CT or magnetic resonance imaging (MRI) can also provide sufficient evidence to make a diagnosis if clinical prediction has not been confirmed (Anderson et al 2009;Kao et al 2014). CT and MRI methods allow more accurate and rapid diagnosis by dint of sectional imaging (Febronio et al 2012;Kao et al 2014). Indeed, CT and MRI play increasingly important roles in the diagnosis of ectopic pregnancies (Febronio et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…This objective can be very challenging, however, because the clinical symptoms, physical examination, and laboratory tests of omental pregnancy are nonspecific, and approximately half of abdominal cases can be sonographically occult [5]. In such situations, CT might be inadvertently used for evaluation and diagnosis, especially for patients in an unstable condition [6] (as in our case). With increasing use of CT scans in emergency departments, it is increasingly important for radiologists to know the CT features of ectopic pregnancy.…”
Section: Discussionmentioning
confidence: 97%
“…The present study revealed a mass in the right hepatic lobe for which the peripheral portion had increased glucose metabolism (SUVmax, 5.7) while the central portion did not exhibit increased glucose metabolism. Familiarity with the typical and atypical US, CT, MRI and PET-CT appearances of various forms of ectopic pregnancy facilitates the prompt and accurate diagnosis and treatment of this condition (43). (44).…”
Section: Discussionmentioning
confidence: 99%